An investigation into the perceived sanitation challenges in the Eastern Cape rural communities - Nancy Phaswana-Mafuya (AOSIS, 2006)
There is a dearth of information on studies that have sought to examine qualitatively the sanitation challenges that rural communities experience. Opsomming Kwalitatiewe navorsing is gedoen om die strukturele, ekonomiese, opvoedkundige, sosiale en tegnologiese uitdagings wat landelike gemeenskappe van die Oos-Kaap met betrekking tot sanitasie in die gesig staar, te ondersoek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.